European chemical policy and the United States: the impacts of REACH - Ackerman, Frank; Stanton, Elizabeth A.; Massey, Rachel (Medford, MA, 2006)
"The European Union is moving toward adoption of its new Registration, Evaluation and Authorization of Chemicals (REACH) policy, an innovative system of chemicals regulation that will provide crucial information on the safety profile of chemicals used in industry. Chemicals produced elsewhere, such as in the United States, and exported to Europe will have to meet the same standards as chemicals produced within the European Union. What is at stake for the U.S. is substantial: we estimate that chemical exports to Europe that are subject to REACH amount to about $14 billion per year, and are directly and indirectly responsible for 54,000 jobs. Revenues and employment of this magnitude dwarf the costs of compliance with REACH, which will amount to no more than $14 million per year. Even if, as the U.S. chemicals industry has argued, REACH is a needless mistake, it will be far more profitable to pay the modest compliance costs than to lose access to the enormous European market."